AB0004 Polymorphisms in Genes in The IL-17 Pathway and B Cell Mediated Immune Response Modulate The Development of Specific Autoimmune Manifestations in Systemic Lupus Erythematosus. (15th July 2016) - Perricone, C.; Ciccacci, C.; Ceccarelli, F.; Cipriano, E.; Alessandri, C.; Spinelli, F.R.; Rufini, S.; Politi, C.; Latini, A.; Novelli, G.; Valesini, G.; Borgiani, P.; et al.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease in which a complex interaction between genetic, environmental and immunological factors determines the susceptibility and the phenotype. Dysregulations in IL-17 pathway as well as in B-cell mediated immune response have been observed in SLE. We have recently demonstrated that polymorphisms in TRAF3IP2 gene are associated with susceptibility for SLE and can predispose for the development of pericarditis (1). TRAF3IP2 encodes for Act1, a molecule that acts as a negative regulator of B cell by inhibiting CD40-mediated signaling and as a positive signaling adapter in IL-17-mediated cellular responses. TRAF6 is essential for the IL-17/Act1-mediated activation of NF-kB, while CD40 is the target for the Act1 mediated inhibition of B cell response. Objectives: The primary goal of our study was to evaluate the association of polymorphisms in CD40, TRAF6 and TNFSF4 (OX40) genes with susceptibility to SLE. Secondary objectives were to assess the possible association of these polymorphisms with the clinical and laboratory features. Methods: We recruited 315 Italian SLE patients and 278 healthy controls. Genotyping of rs4810485 in CD40, rs4755453 and rs5030437 in TRAF6, and rs2205960 and rs10489265 in TNFSF4 (OX40) SNPs was performed by allelic discrimination assay. A case/control association study and a genotype/phenotype correlation analysis were performed. Results: Deviations from Hardy–Weinberg equilibrium for the three SNPs were not observed. None of the studies polymorphisms was associated with susceptibility for SLE. Only CD40 rs4810485 was associated at genotypic (P=0.034) but not at the allelic level. Nonetheless, these polymorphisms seem to contribute to define disease phenotype. TRAF6 was associated with the presence of anemia (P=0.019, OR=1.96), rs2205960 of TNFSF4 was associated with the pericarditis (P=0.013, OR=2.14), and rs4810485 of CD40 with the presence of anti-SSB/La (P=0.014, OR=2.26) and lupus nephritis (P=0.024, OR=1.8). Conclusions: We were not able to confirm previous association of TRAF6 and CD40 polymorphisms with susceptibility for SLE. However, such SNPs seem to influence the disease phenotype. In particular, it is of interest the association of rs4810485 in CD40 with lupus nephritis and the presence of anti-SSB/La. Indeed, the modulation of CD40-mediated T cell-dependent antibody response has already been associated with the development of anti-SSB/La in association with SLE-like nephritis in a mouse model (2), probably due to an uncontrolled B cell activation signal. References: Perricone C, Ciccacci C, Ceccarelli F, et al. TRAF3IP2 gene and systemic lupus erythematosus: association with disease susceptibility and pericarditis development. Immunogenetics. 2013 Oct;65(10):703–9 Qian Y, Giltiay N, Xiao J, et al. Deficiency of Act1, a critical modulator of B cell function, leads to development of Sjögren's syndrome. Eur J Immunol. 2008 Aug;38(8):2219–28. Disclosure of Interest: None declared